Pengaruh Kualitas Pelayanan, dan Penetapan Harga Terhadap Keputusan Pembelian Sepeda Motor Vario 150 Pada PT. Gratia Plena Mas Motor Cabang Lahat - Markus, Markus (Universitas Muhammadiyah Palembang, 2019)
ABSTRACT Purpose - This study aims to determine the effect of Service Quality on Purchasing Decisions of Honda Vario 150 Motorcycles at PT. Gratia Plena Mas Lahat Branch, the effect of Pricing on the Purchase Decision of Honda Vario 150 Motorcycles at PT. Gratia Plena Mas Lahat Branch, and Service Quality and Pricing on the Purchase Decision of Honda Vario 150 Motorcycle at PT. Gratia Plena Mas Lahat Branch.Design/methodology - The sample in this study amounted to 50 respondents who were distributed to consumers specifically motorcycle products with the brand